Analisis Produktivitas Usaha Penangkapan Nelayan Trammel Net di Desa Arung Parak Kecamatan Tangaran Kabupaten Sambas : Productivity Analysis of Trammel Net Fishing Business in Arung Parak Village Tangaran District Sambas Regency - Wahyuni, Rosa; Merdekawati, Dewi; S, Indra Mahyudi (Journal of Fisheries and Marine Applied Science, 2024)
The Trammel net is a type of gill net fishing gear that has three layers of gill nets with the aim of cathching demersal fish and shrimp. The purpose of this study was to determine the level of productivity and the profit generated by the trammel net fishing business in Arung Parak Village, Tangaran District, Sambas Regency. This study used a descriptive analysis method by conducting surveys and direct interviews with fishermen in Arung Parak Village from May to June 2023. Data collection for the study was 4 trips with a sample of 36 trammel-net fishermen. The data analysis in this study is an analysis of productivity, costs, revenue, and profits/losses from fishing efforts. Based on the results of this study, the trammel net fishing business in Arung Parak Village has a productivity value 0f 9,445/trip with an average profit of IDR 799.063 from fishing activities, indicating that the fishing business is profitable and feasible